Squamous cell carcinoma arising from an epidermal cyst in the thumb. (2015) - Sakamoto, Akio; Shiba, Eisuke; Hisaoka, Masanori
Highlights: Squamous cell carcinoma arising from an epidermal cyst is rare. The most frequently affected region is the head and neck. In contrast, involvement of the fingers is extremely rare. The clinical symptoms of squamous cell carcinoma arising from an epidermal cyst can mimic those of an infected epidermal cyst. The current report facilitates awareness of such disease. Abstract: Introduction: Squamous cell carcinoma arising from an epidermal cyst is rare, and the most frequently affected region is the head and neck. Presentation of case: A 41-year-old man noticed swelling and a small ulceration in the thumb pulp. A lesion with a 2-cm diameter was simply resected based on a diagnosis of infected epidermal cyst. Pathological diagnosis of the resected material was squamous cell carcinoma arising from an epidermal cyst. Consequent amputation was performed. Discussion and conclusion: The clinical symptoms of squamous cell carcinoma arising from an epidermal cyst can mimic those of an infected epidermal cyst. The current report facilitates awareness of such disease.